Skip to content
#
Solve for x: 3(x + 1) = 5(x − 2) + 7.

8
0
0

A
3

3(x + 1) = 5(x − 2) + 7

3x + 3 = 5x − 10 + 7

3x + 3 = 5x − 3

3x + 6 = 5x

6 = 2x

3 = x

Explaination

Begin by distributing the 3 and the 5 through their respective parentheses, then combine like terms on each side of the equal sign: 3(x + 1) = 5(x − 2) + 7

3x + 3 = 5x − 10 + 7

3x + 3 = 5x − 3

3x + 6 = 5x

6 = 2x

3 = x

B −2

C 2

D $1435_w9_h37.png$

Take more free practice tests for other ASVAB topics with our free practice asvab now!